Pencegahan kekerasan rumah tangga perspektif Islam - Wardah, Rahmanialfi (Maliki Interdisciplinary Journal, 2025)
Domestic violence (DV) is an act of violence that occurs in the family, involving physical, sexual, psychological, poverty, and neglect, which often ends in prolonged trauma for the victim. Although often misunderstood as only physical violence, DV includes emotional, verbal, and economic control. Islam teaches men and women to love and care for each other, and to prevent acts of domestic violence. The researcher's goal is to prevent domestic violence based on Islamic advice. All Muslim families can prevent violence and domestic violence by understanding the roles and responsibilities in the family, maintaining good communication, patience and tolerance, and following the traditions of the Prophet Muhammad SAW. Living in harmony It is important for every Muslim to always get closer to God Almighty and praise his religion and always ask for guidance from Him in his household life. Thus, God willing, the family becomes a safe, harmonious and loving place according to Islamic guidelines.